ANI scoring system – In differentiating alcoholic and non-alcoholic liver disease - Anitha G; Sivakumar J; Ponniraivan, Kalavathy (Asian Journal of Medical Sciences, 2021)
Background: Alcoholic liver disease/non-alcoholic liver disease Index – ANI scoring system was constructed for clinically diagnosing the etiology of liver diseases, avoiding the risks of liver biopsy. Aims and Objectives: This study aims to test the reliability of ANI scoring system as a non-invasive method to distinguish alcoholic liver disease (ALD) from non-alcoholic fatty liver disease (NAFLD). Materials and Methods: This retrospective study was conducted on 177 (114 men and 58 women) treated as inpatients in Trichy SRM Medical College Hospital and Research Centre, Trichy, in the period of December 1, 2015–August 1, 2016. About 40 patients with etiology of viral, autoimmune, and biliary lithiasis were excluded. A total of 137 patients (98 men and 39 women) were classified into two groups, ALD (70) and NAFLD (67) based on diagnosis. Parameters of ANI – AST, ALT, MCV, BMI, and sex were recorded. ANI was calculated by online calculator. Results: ANI was significantly higher in patients with ALD than NAFLD (P<0.01). The cutoff value of ANI is –0.11. Conclusion: On the basis of the results, ANI scoring system may be used in clinically distinguishing ALD from NAFLD, avoiding the risks of liver biopsy.